Isolation and characterization of a catalase-negative strain of Staphylococcus aureus. - Tu, K K (1976)
An unusual, naturally occurring strain of Staphylococcus aureus is characterized. It is typical in colony and cellular morphology, coagulase production, and other biochemical reactions as compared to S. aureus (ATCC-25923), except that it is catalase negative and fails to ferment mannitol anaerobically.